(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
This study aims to develop recommendations for the introduction of a new sample of motor oils specifically designed for military equipment and to determine their effectiveness compared to existing options. Motor oils play a critical role in the performance and longevity of military vehicles, and selecting the optimal oil is crucial for operational readiness and cost efficiency. The research involved both laboratory and field tests to evaluate the viscosity, thermal stability, and overall performance of the new motor oil samples under various conditions. Key findings indicate that the new motor oil samples offer superior thermal stability and maintain optimal viscosity across a wider range of temperatures, leading to improved performance and reduced maintenance needs. Based on these findings, the study recommends the adoption of these new motor oil samples for military equipment. The implementation plan includes phased testing, training for maintenance personnel, and continuous monitoring to ensure long-term effectiveness and adaptability to different operational environments.